2023
DOI: 10.3233/jad-230124
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Between Hippocampal Parenchymal Fraction and Cortical Grey Matter Atrophy at Different Stages of Cognitive Decline

Abstract: Background: Hippocampal atrophy is a significant brain marker of pathology in Alzheimer’s disease (AD). The hippocampal parenchymal fraction (HPF) was recently developed to better assess the hippocampal volumetric integrity, and it has been shown to be a sensitive measure of hippocampal atrophy in AD. Objective: To investigate the clinical relevance of hippocampal volumetric integrity as measured by the HPF and the coupling between the HPF and brain atrophy during AD progression. Methods: We included data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Notably, the MTL is recognized as one of the earliest sites of atrophy [7] and tau tangle pathology [8]. Previous research has demonstrated strong relationships between gray matter integrity of the MTL, such as hippocampal volume [9,10], and disease progression. Further, MTL regions have been shown to have declining WM microstructure associated with normal aging [11].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the MTL is recognized as one of the earliest sites of atrophy [7] and tau tangle pathology [8]. Previous research has demonstrated strong relationships between gray matter integrity of the MTL, such as hippocampal volume [9,10], and disease progression. Further, MTL regions have been shown to have declining WM microstructure associated with normal aging [11].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating literature has suggested that atrophy of hippocampus is closely linked to cognitive decline in normal aging and the progression of Alzheimer’s disease (AD) ( Hampel et al, 2008 ; Shi et al, 2009 ; Frisoni et al, 2010 ; Mu and Gage, 2011 ; Xiao et al, 2023 ). Indeed, the hippocampus, known to play a crucial role in the formation, organization, and consolidation of new memories, is one of the earliest structures that are vulnerable to atrophy in normal aging, and it also has been acknowledged as the core biomarker for the pathological changes of mild cognitive impairment (MCI) and AD ( Mu and Gage, 2011 ).…”
Section: Introductionmentioning
confidence: 99%